Residual β-Cell Function in Type 1 Diabetes Followed for 2 Years after 3C Study - Kun Lin; Xiaoping Yang; Yixi Wu; Shuru Chen; Qiong Zeng (Journal of Diabetes Research)
Objective. To investigate the natural history and related factors of the pancreatic β-cell function in Chinese type 1 diabetic patients from 3C study Shantou center. Method. Stimulated C-peptide levels from follow-up data of 201 individuals in 3C study Shantou subgroup starting in 2012 were used. Residual β-cell function was defined as stimulated C−peptide level≥0.2 pmol/mL, on the basis of cut-points derived from the Diabetes Control and Complications Trial (DCCT). Results. 36.8% of patients had residual β-cell function, and the percentage was 68.2% in newly diagnosed diabetic patients. COX regression analysis indicated that the age of diagnosis, HbA1C level, and duration were independent factors of residual β-cell function in individuals with ≤5 years duration, but in those with duration ≥5 years, only the age of diagnosis was a predictor. The pancreatic β-cell function mainly declined in the first 5 years of the duration, and the rate of decline was correlated negatively with the duration and age of diagnosis. Receiver operating characteristic (ROC) analysis indicated that the cut-off point of stimulated C-peptide was 0.615 pmol/mL in patients with <5 years duration to have 7% HbA1c. Conclusion. Age at diagnosis was the strongest predictor for residual C-peptide. There was a more rapid decline of stimulated C-peptide in duration ≤5 years and younger patients. Therefore, intervention therapies of β-cells should start from the early stage, and the recommended target goal of stimulated C-peptide is 0.615 pmol/mL or above.